Auditory cortex activity related to perceptual awareness versus masking of tone sequences - Gärtner, Kai; Gutschalk, Alexander (NeuroImage, 2021)
Sequences of repeating tones can be masked by other tones of different frequency. When these tone sequences are perceived, nevertheless, a prominent neural response in the auditory cortex is evoked by each tone of the sequence. When the targets are detected based on their isochrony, participants know that they are listening to the target once they detected it. To explore if the neural activity is more closely related to this detection task or to perceptual awareness, this magnetoencephalography (MEG) study used targets that could only be identified with cues provided after or before the masked target. In experiment 1, multiple mono-tone streams with jittered inter-stimulus interval were used, and the tone frequency of the target was indicated by a cue. Results showed no differential auditory cortex activity between hit and miss trials with post-stimulus cues. A late negative response for hit trials was only observed for pre-stimulus cues, suggesting a task-related component. Since experiment 1 provided no evidence for a link of a difference response with tone awareness, experiment 2 was planned to probe if detection of tone streams was linked to a difference response in auditory cortex. Random-tone sequences were presented in the presence of a multi-tone masker, and the sequence was repeated without masker thereafter. Results showed a prominent difference wave for hit compared to miss trials in experiment 2 evoked by targets in the presence of the masker. These results suggest that perceptual awareness of tone streams is linked to neural activity in auditory cortex.
Gesehen am 25.03.2021